Agricultural Insurance Models in Banyumas, Indonesia: Potentials, Problems, and Challenges : Model Asuransi Pertanian di Banyumas, Indonesia : Potensi, Permasalahan, dan Tantangan - Zumaeroh; Anisa, Faefaya Ziadatul; Purnomo, Sodik Dwi; Retnowati, Diah; Adhitya, Bagus (Procedia of Social Sciences and Humanities, 2022)
Farming businesses are constantly faced with the risk of uncertainty due to climate change. The risk of uncertainty affected the destruction of farming infrastructure and a high level of crop failure. Furthermore, the research objective was to 1) identify the potential of the agricultural sector in Panusupan Village, Cilongok District Banyumas Regency, 2) analyze the factors that influence farmers' interest in participating in the insurance program in Panusupan Village, Cilongok District Banyumas Regency, 3) identify the inhibiting and driving factors in farmers participating in the agricultural insurance program in Panusupan Village, Cilongok District Banyumas Regency, 4) identify the stakeholders involved in the development of agricultural insurance in Panusupan Village, Cilongok District Banyumas Regency, and 5) formulate agricultural insurance development models in Panusupan Village, Cilongok District Banyumas Regency. This research applied a mixed-method approach of qualitative and quantitative approaches. Additionally, the research methods were the Miles and Huberman approach and binary logistic regression analysis. The research population consisted of farmers in Panusupan Village, Cilongok District Banyumas Regency. The research results indicated that Panusupan Village could join the agricultural insurance program seen from the extensive agricultural land and could be pretty good. It can be seen from the amount of land used; farmer groups classified as active; people whose jobs were primarily farmers; and many agencies that provided agricultural insurance socialization. The binary logistic regression results showed that age, education, income, number of family dependents, land area, farming experience, the intensity of crop failure, socialization participation had significant effects on farmers' interest in participating in agricultural insurance programs in Panusupan Village, Cilongok District Banyumas Regency. Technology had no significant effect on farmers' interest in participating in the agricultural insurance program in Panusupan Village, Cilongok District Banyumas Regency. Barriers and drivers in the development of agricultural insurance included internal and external factors.